Quality academic process: a panacea for student development in university education (2018)
There has been a discussion on the quality of student development in the Nigerian university system as one of the roles of university education, is a manpower development. However, there has been a decline in the quality of graduates produced. This study was carried out to determine the impact of quality academic process on student development. The study adopted a survey research method where an instrument titled quality academic process questionnaire (QAPQ) and student development questionnaire (SDQ) were administered on faculty members in public universities in Nigeria. Out of 450 questionnaires that were given out, only 305 were returned and usable for data analysis after the data cleaning. The findings of the study revealed that university curriculum, instruction, assessment, research and development significantly determined the quality of student development while service learning was found not to be significantly related to student development. Therefore, some practical and theoretical implications were made and future research directions were suggested.